2019
DOI: 10.1038/s41467-018-08249-9
|View full text |Cite
|
Sign up to set email alerts
|

Amide nitrogen pyramidalization changes lactam amide spinning

Abstract: Although cis-trans lactam amide rotation is fundamentally important, it has been little studied, except for a report on peptide-based lactams. Here, we find a consistent relationship between the lactam amide cis/trans ratios and the rotation rates between the trans and cis lactam amides upon the lactam chain length of the stapling side-chain of two 7-azabicyclo[2.2.1]heptane bicyclic units, linked through a non-planar amide bond. That is, as the chain length increased, the rotational rate of trans to cis lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…In addition to twisting, amide bond geometric distortion can be achieved by pyramidalization of the nitrogen atom. In the extreme cases, these pyramidalized amides feature sp 3 hybridization that is more characteristic to amines rather than amides. , The most well-known examples of such pyramidalized amides include confining the amide bond nitrogen in a cyclic ring system, such as azetidine or aziridine, however, in these moieties, the inherent ring strain of the small-ring heterocycle contributes to the reactivity of these amides . Recent elegant studies by Ohwada and co-workers identified 7-azabicyclo[2.2.1]­heptane amides (such as 5.7 , Figure ) as another class of fully pyramidalized amides. …”
Section: Cyclic Amides: N-pyramidalization 40–60°mentioning
confidence: 99%
“…In addition to twisting, amide bond geometric distortion can be achieved by pyramidalization of the nitrogen atom. In the extreme cases, these pyramidalized amides feature sp 3 hybridization that is more characteristic to amines rather than amides. , The most well-known examples of such pyramidalized amides include confining the amide bond nitrogen in a cyclic ring system, such as azetidine or aziridine, however, in these moieties, the inherent ring strain of the small-ring heterocycle contributes to the reactivity of these amides . Recent elegant studies by Ohwada and co-workers identified 7-azabicyclo[2.2.1]­heptane amides (such as 5.7 , Figure ) as another class of fully pyramidalized amides. …”
Section: Cyclic Amides: N-pyramidalization 40–60°mentioning
confidence: 99%
“…This enhancement is particularly large for the Fp-based macromolecules due to the presence of highly polar Fp–acyl groups in the repeating units (Scheme a,b). The ring structure restricts the chain conformation and thus the rotation of the polar groups in the repeating units, which minimizes the cancellation of the dipole moments caused by the antiparallel alignment of the polar Fe–acyl groups. An all-atom simulated configuration of P­( P FpR) 30 macrocycles is illustrated in Figure S2, from which the angles between CO (in Fe–acyl groups) and the plane of the macrocycle are calculated and plotted in Figure b. As shown in the figure, only 8.7% of the angles are larger than 90°, which suggests that most of the polar CO groups point to one side of the ring plane and thus effectively enhance the overall polarity of the macrocycles.…”
Section: Resultsmentioning
confidence: 99%
“…Amide cis trans Isomerization From the NMR spectra in CD 2 Cl 2 , the cis/trans ratio of the amide of the dimer (16(C8) 20(C12)) was estimated. 32 It was found that the ratio varied signi cantly with the length of the linker (Figure 11). As the linker length increases, the ratio of cis amides increases, changing from almost exclusively trans (6(Z) NH (C8), 99.9% trans, K t/c 999) to predominantly cis (20(C12), 94% cis, K t/c 0.06).…”
Section: Spinning Features Of Bicyclic Dimer Lactamsmentioning
confidence: 99%